2013
DOI: 10.5858/arpa.2012-0048-oa
|View full text |Cite
|
Sign up to set email alerts
|

Steatohepatitic Hepatocellular Carcinoma, a Morphologic Indicator of Associated Metabolic Risk Factors: A Study From India

Abstract: Context.-The common risk factors for hepatocellular carcinoma (HCC) include persistent viral infection with either hepatitis B or C virus, alcohol abuse, hemochromatosis, and metabolic syndrome. Steatohepatitic (SH) HCC has been recently recognized as a special morphologic variant of HCC associated with metabolic risk factors.Objective.-To assess the SH pattern in HCC cases of various etiologies in Indian patients and to further correlate this morphology with the presence of metabolic risk factors.Design.-A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 23 publications
7
76
2
Order By: Relevance
“…Our cohort with predominantly HBV‐infected Chinese patients (83.5%) was able to fill the potential knowledge gap. Our findings were largely consistent with those described previously and reinforced the distinguishing clinical association of steatohepatitic HCC with underlying fatty liver, steatohepatitis and metabolic risk . However, we demonstrated that steatotic HCC also has a characteristic association with underlying fatty liver, steatohepatitis and metabolic risks.…”
Section: Discussionsupporting
confidence: 92%
“…Our cohort with predominantly HBV‐infected Chinese patients (83.5%) was able to fill the potential knowledge gap. Our findings were largely consistent with those described previously and reinforced the distinguishing clinical association of steatohepatitic HCC with underlying fatty liver, steatohepatitis and metabolic risk . However, we demonstrated that steatotic HCC also has a characteristic association with underlying fatty liver, steatohepatitis and metabolic risks.…”
Section: Discussionsupporting
confidence: 92%
“…When examining patient characteristics, the steatohepatitic HCC variant patients showed higher numbers of metabolic syndrome risk factors as well as at least 3 components of metabolic syndrome[116]. In a separate study, Jain et al[118] found the steatohepatitic variant of HCC (SH-HCC) in approximately 19% of their cases over a period of 7 years, with 50% of those cases being seen in NAFLD patients and the other 50% were largely of HCV etiology. It is important to note, in a study performed by Yeh et al[119], that SH-HCC can occur outside the morphology of that seen in fatty liver disease or metabolic syndrome and was posited to be more likely attributable to genetic changes of shared genes or metabolic pathways.…”
Section: Histopathologymentioning
confidence: 99%
“…Another study from India by Jain et al in 2013 also illustrated similar association of SH-HCC with the metabolic syndrome [6].…”
Section: Discussionmentioning
confidence: 71%